STUDENT LOYALTY IN PRIVATE SECONDARY EDUCATION: THE ROLES OF SERVICE QUALITY, SATISFACTION, AND COMPETITOR INTENSITY - Hasnawati Hasnawati; Mona Novita; Najmi Diyana Lathifah (PEDAGOGIK : JURNAL PENDIDIKAN, 2025)
Private secondary schools increasingly face competitive pressure as students and parents compare institutions based not only on academic provision but also on service quality, teacher competence, institutional value, and alternative school options. This study examines how educational staff services and teacher competence influence student loyalty through student satisfaction and whether competitor intensity strengthens the satisfaction–loyalty relationship. A quantitative explanatory survey was conducted with 315 students from private senior high schools in a highly competitive urban educational market. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that both educational staff services and teacher competence significantly enhance student satisfaction, with teacher competence showing the stronger effect. Student satisfaction significantly increases student loyalty and partially mediates the effects of both educational staff services and teacher competence on loyalty. Furthermore, Competitor Intensity significantly strengthens the relationship between student satisfaction and student loyalty, indicating that satisfaction becomes more consequential for loyalty when students perceive stronger school competition.